The effects of melatonin on brain nitrosative stress and energy balance in fructose-mediated metabolic syndrome model - Ozan, Gonca; Bircan, Filiz Sezen; Topal, Turgut; Turkozkan, Nurten (Walter de Gruyter Gmbh, 2016)
Objective: Metabolic syndrome (MetS), one of the common health problems seen with increasing frequency in today's modern societies, is also a important risk factor for neurological disorders such as stroke, depression, Alzheimer's disease. On the other hand, melatonin is a neurohormone, has potent antioxidant and neuroprotective activities. In the present study, we aimed to investigate the possible protective effects of melatonin administration on brain tissue in fructose-mediated MetS model. Methods: Male adult Sprague-Dawley rats were randomly divided into four groups (n=8); control, fructose, melatonin and fructose plus melatonin. MetS was induced by fructose solution 20% in tap water, and melatonin was administered at the dose of 20 mg/kg bw/day by oral gavage. Systolic blood pressures (SBP) were measured by tail-cuff method. After the experimental period of 8 weeks, serum triglyceride, glucose, insulin, and tissue ATP/ADP ratio, nitric oxide (NOx) and 3-nitrotyrosine (3-NT) levels were measured. Also tissue endothelial and inducible nitric oxide synthase (eNOS and iNOS) protein levels were determined. Results: Fructose consumption increased SBP, serum triglyceride, insulin levels and induced insulin resistance significantly compared to control group and MetS model was successfully demonstrated. In comparison with control group, fructose administration did not cause significant changes in tissue ATP/ADP ratio and 3-NT levels. NOx levels did not change significantly among groups, and iNOS-eNOS proteins were not detected in any groups. Interestingly, tissue 3-NT levels were elevated significantly while ATP/ADP ratio was diminished in fructose plus melatonin group compare with both control and fructose groups. Conclusion: These results indicate that high fructose diet for 8 weeks does not influence nitric oxide production, energy metabolism and protein nitration in brain. Nevertheless melatonin acted as a pro-oxidant at that dose when administered with fructose.
Keywords: Fructose; metabolic syndrome; melatonin; brain; energy